Gender, sexuality and violence: perception of mobilized adolescents in an online game - Rosa Maria Godoy Serpa da Fonseca; Danyelle Leonette Araújo dos Santos; Rafaela Gessner; Lucimara Fabiana Fornari; Rebeca Nunes Guedes de Oliveira; Michaela Chiara Schoenmaker
ABSTRACT Objective: To identify and analyze the perception of high school students about violence in intimacy relations in adolescence, in the light of the category Gender. Method: A qualitative, descriptive and exploratory study, based on the comments of 27 adolescents participating in the online game, Papo Reto. The discourses were submitted to the analysis of thematic content and discussed in the light of the category Gender. Results: Adolescents naturalize violence in their relationships of intimacy, but when they recognize it, they react in several ways: with aggressions, dialoguing with the partner or seeking support from third parties. Final considerations: There were discordant perceptions regarding the phenomenon, most of which reiterated gender stereotypes. However, they reveal attitudes favorable to overcoming mainly related to the attainment of autonomy.